Highly Oriented Electrospun Conductive Nanofibers of Biodegradable Polymers-Revealing the Electrical Percolation Thresholds - Munawar, Muhammad; Schubert, Dirk W. (6th European Symposium on Biomaterials and Related Areas BioMAT 2021, 2021)
An electrospinning process with a special rotating collector electrode is used to generate highly oriented electrospun conductive fiber composites (ECFCs) of biodegradable polymers. Poly(ethylene oxide) (PEO), polycaprolactone (PCL), and polylactic acid (PLA) are blended with intrinsically conductive polymers (ICPs) fillers of poly(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline (PANi). As the proportion of filler increases, the number of “conductive pathways” grow, and consequently the conductivity of the ECFCs also increases. A procedure is developed for calculating the volume fraction (φ) of filler, density, and conductivity of electrospun nanofibers. The conductivity as a function of filler fraction is shown and described by using a McLachlan equation for the first time to reveal the electrical percolation thresholds (φc) of nanofibers. During the annealing process, a buildup of additional conductive channels within ECFCs is responsible for increasing inter and intrachain conductivities among fillers and matrices. Therefore, annealed ECFCs transport charge more efficiently due to an increase in continuous pathways, which lead to superior electrical conductivity and lowering the percolation threshold. Moreover, a time–temperature effect on percolation thresholds of ECFCs is evident. The compatibility between filler and matrix and the inherent conductivity of filler and molar mass of matrix are among significant factors for determining φc. The fiber diameter and conductivity of ECFCs are both tunable. The comparative study shows that these highly oriented electrospun conductive nanofibers have great potential in various biomedical application